+0  
 
0
44
1
avatar

How to Convert these two functions?

 

 
Guest Dec 7, 2017

Best Answer 

 #1
avatar+5552 
+1
1.      f(x)  =  2(x - 1)

        

Using the rule   \(\frac{x^a}{x^b}=x^{a-b}\)  , we have
  f(x)  =  \(\frac{2^x}{2^1}\)

 

 

 
  f(x)  =  \(\frac{2^x}{2}\)

 

 
  f(x)  =  \(\frac12\cdot2^x\)

 

 

Here,   a = 1/2   and   b = 2  .
   

 

 

 
2. f(x)  =  2(3x + 4)

 

Using the rule   xa · xb  =  x(a + b)  , we have
  f(x)  =  23x · 24

 

 

 
  f(x)  =  23x · 16

 

Using the rule   (xa)b  =  xab  , we have
  f(x)  =  (23)x · 16

 

 

 
  f(x)  =  16 · 8x   Here,   a = 16   and   b = 8  .
 
hectictar  Dec 7, 2017
Sort: 

1+0 Answers

 #1
avatar+5552 
+1
Best Answer
1.      f(x)  =  2(x - 1)

        

Using the rule   \(\frac{x^a}{x^b}=x^{a-b}\)  , we have
  f(x)  =  \(\frac{2^x}{2^1}\)

 

 

 
  f(x)  =  \(\frac{2^x}{2}\)

 

 
  f(x)  =  \(\frac12\cdot2^x\)

 

 

Here,   a = 1/2   and   b = 2  .
   

 

 

 
2. f(x)  =  2(3x + 4)

 

Using the rule   xa · xb  =  x(a + b)  , we have
  f(x)  =  23x · 24

 

 

 
  f(x)  =  23x · 16

 

Using the rule   (xa)b  =  xab  , we have
  f(x)  =  (23)x · 16

 

 

 
  f(x)  =  16 · 8x   Here,   a = 16   and   b = 8  .
 
hectictar  Dec 7, 2017

25 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details